Bronchoscopy masks mitigate aerosols during upper gastrointestinal endoscopies - Phillips, Frank; Crowley, Jane; Warburton, Samantha; Parra-Blanco, Adolfo; Gordon, George S. D. (Endoscopy International Open, 2023)
Background and study aims Upper gastrointestinal endoscopies are considered aerosol-generating procedures (AGP) that risk spread of airborne diseases such as SARS-CoV-2. We aimed to investigate where clinically approved bronchoscopy masks applied to patients during esophagogastroduodenoscopies can mitigate spread of aerosols and droplets.Patients and methods This study included patients undergoing routine upper gastrointestinal endoscopy in a standard endoscopy room and used a particle counter to measure size and number of particles 10 cm from the mouths of 49 patients undergoing upper gastrointestinal endoscopies, of whom 12 wore bronchoscopy masks and 37 did not (controls). Particle counts in the aerosol (≤ 5 µm diameter) and droplet (> 5 µm-diameter) size ranges were measured and averaged over the duration of procedures.Results The use of bronchoscopy masks offers a 47% reduction (P = 0.01) in particle count for particles < 5 μm in diameter over the procedure duration (aerosols).Conclusions Bronchoscopy masks or similar are a simple, low-cost mitigation technique that can be used during outbreaks of respiratory diseases such as COVID-19 to improve safety and reduce fallow times.
Keywords: Quality and logistical aspects; Hygiene; Endoscopy Upper GI Tract; Quality management